Green synthesis of silver nanoparticles using white sugar. Issue 1 (1st March 2013) - Meshram, Sachin M.; Bonde, Shital R.; Gupta, Indarchand R.; Gade, Aniket K.; Rai, Mahendra K.
Abstract : Till date several methods of chemical synthesis of silver nanoparticles (AgNps) are known. Most of the protocol dealing with the chemical synthesis of AgNps involves high pressure, temperature, energy and technical skills. Thus, a method with much greener approach is the need of the hour. Accordingly, the authors have developed a method that is cost‐effective, energy‐efficient and easy method for the synthesis of AgNps. The AgNps were synthesised by using white sugar and sodium hydroxide (NaOH) in the presence of sunlight. These nanoparticles were characterised by visual observation, ultraviolet–visible (UV–vis) spectrophotometry, Fourier transform infrared (FTIR), nanoparticle tracking and analysis (NTA) and transmission electron microscopy (TEM). The effect of NaOH on the rate of AgNps synthesis was also studied. Formation of AgNps was primarily detected by change in colour of reaction mixture from colourless to yellow after treatment with 1 mM silver salt (AgNO3 ). UV–vis spectroscopy showed peak at 409 nm. NTA revealed the polydispersed nature of nanoparticles, 15–30 nm in diameter. FTIR showed the presence of gluconic acid as capping agent, which increases the stability of AgNps in the colloids. TEM demonstrated the presence of spherical AgNps in the range of 10–25 nm. The present method confirms the synthesis of AgNps by using white sugar and NaOH. This method is simple, eco‐friendly and economically sustainable, making it amenable to large‐scale industrial production of AgNps.